2017
DOI: 10.1016/j.seizure.2017.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and neurodevelopmental outcome of new-onset acute symptomatic seizures in children

Abstract: CNS infections are the most common cause of ASS in children from developing countries. Abnormal neurodevelopment and seizure recurrences on short-term follow-up are seen in a minority of children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…However, identifying the causative pathogen in brain infections in children is crucial not only for treatment but also for neurodevelopmental prediction (19, 20). We focused on only three pathogenic organisms and found that Enterovirus accounted for the majority of brain infections, followed by GBS, S .…”
Section: Discussionmentioning
confidence: 99%
“…However, identifying the causative pathogen in brain infections in children is crucial not only for treatment but also for neurodevelopmental prediction (19, 20). We focused on only three pathogenic organisms and found that Enterovirus accounted for the majority of brain infections, followed by GBS, S .…”
Section: Discussionmentioning
confidence: 99%